Pengaruh Konsumsi Fast Food terhadap Risiko Obesitas pada Remaja di Berbagai Negara dan Wilayah Daerah - Ghalin Annisa Widiya; Andriyani Andriyani; Nurmalia Lusida (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The fast-paced modern lifestyle has led teenagers to favor fast food over healthier home-cooked meals. This study aims to analyze the effects of fast food consumption on obesity risk among adolescents through a review of 20 relevant studies. The findings indicate that excessive consumption of fast food, along with low physical activity and social influences, significantly contributes to the increasing rates of adolescent obesity in Indonesia. Key factors include easy access, affordability, aggressive marketing, sedentary lifestyles, and a lack of nutritional education. As a result, there is a heightened risk of degenerative diseases such as type 2 diabetes, hypertension, and heart disease, as well as psychological issues related to low self-esteem. To address the rising trend of adolescent obesity, comprehensive interventions are necessary, including nutrition education, dietary regulation, and the promotion of active lifestyles.